Vineyard chill : a Martha's Vineyard mystery - Craig, Philip R., 1933-2007. (New York : Scribner, 2008)
With two friends in trouble and his own family receiving threats, J.W. Jackson must summon all of his investigative skills to try to restore order to his beloved Vineyard island home, where fishing and good food should always take precedence over murder.
Keywords: Jackson, Jeff (Fictitious character) -- Fiction; Private investigators -- Massachusetts -- Martha's Vineyard -- Fiction; Martha's Vineyard (Mass.) -- Fiction; Mystery fiction